Approach for a realtime training feedback algorithm in skiing - Müller, M.; Ebert, C.; Senner, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In addition to personal feedback of coaches, Video analysis and sole pressure distribution (SPD) are used as objective methods for training control in Professional skiing. The value of SPD was investigated profoundly (Glitsch, 2001, Schöllhorn et al. 2001). There is, however, few information about objective training support in leisure sports. This study aims to introduce basic data to build a realtime training feedback algorithm (RTFA) for carving which can be applied to a simple mobile hardware System.